Precision oncology using a clinician‐directed, tailored approach to molecular profiling. Issue 1 (30th October 2017) - Lam, Michael; Tran, Ben; Beck, Sophie; Tie, Jeanne; Herath, Dishan; Whittle, James; Kwan, Edmond M.; Fox, Stephen B.; Fellowes, Andrew; Ananda, Sumitra; Lipton, Lara; Gibbs, Peter; et al.
Abstract: Aim: Precision oncology involves molecularly matching patients to targeted agents usually in early drug development (EDD) programs. Molecular profiling (MP) identifies actionable targets. Comprehensive commercial MP platforms are costly and in resource limited environments, a more practical approach to MP is necessary to support EDD and precision oncology. We adopted a clinician‐directed, tailored approach to MP to enrol patients onto molecularly targeted trials. We report the feasibility of this approach. Methods: All patients referred to the Royal Melbourne Hospital (RMH) EDD between September 2013 and September 2015 were identified in a prospective database. Key captured data included clinicopathological data, MP platform ordered (if any), molecular targets identified and subsequent enrolment onto clinical trials. EDD‐clinician decisions to order MP and the platform utilized was guided by patient consultation, tumor type, trial availability and requirement for molecular information. Results: We identified 377 patients referred to RMH EDD. A total of 216 (57%) had MP ordered. The remainder had known actionable targets (19%), or were inappropriate for clinical trials (24%). In those undergoing MP, 187 genetic aberrations were found in 113 patients with 98 considered actionable targets in 86 patients. Ninety‐eight (25%) patients were enrolled onto a clinical trial, including 40 (11%) receiving molecularly matched treatments. Median progression‐free survival was improved in patients enrolled onto molecularly matched trials compared to those on unmatched trials (3.6 months vs 1.9 months, HR 0.58 [0.38–0.89], P = 0.013). Conclusion: A clinician‐directed, tailored approach to the use of MP is feasible, resulting in 11% of patients enrolled onto molecularly matched trials.